EMPOWERING YOUTH IN CONTROLLING COVID-19 INFECTION AT THE IRMA AL-KAUTSAR MOSQUE SENOPATI HOUSING, CIKANDE, SERANG REGENCY - Salma Talitha; Hadi Pratomo; Ditya Fahlevi Safitri; Imelda Sussanti Nailius; Muhamad Ridwan; Dzul Fahmi Afriyanto; Wendya Nidsy Revita (Universitas Airlangga, 2023)
Introduction: Since the WHO has stated that the COVID-19 is a pandemic, education and empowerment regarding COVID-19 in youths is needed. The purpose of this study is to explain the effect of providing online education on behavior and the process of empowering the youth of the Irma Al-Kautsar Mosque regarding the COVID-19 prevention protocol. Method: A mixed method was conducted in this study. Case study design was used for qualitative method and quasi-experimental design for quantitative. Total sampling was used on the population, which was youths aged 14-18 years (N=10). The data collection and retrieval techniques are group discussions and questionnaires about behavior. Results: The study showed that the group discussion resulted in three big themes, namely related to the COVID-19 prevention and education program, the needs of youth for education about COVID-19, and effective methods of disseminating COVID-19 information for youths. It showed a change in the frequency and percentage of behavior regarding COVID-19 and the prevention of infection in youths. The paired t-test showed that the knowledge domain had a significance value p <0.05 and for the action and attitude domain was p> 0.05. Conclusions: There was a significant influence between providing education with knowledge improvement related to COVID-19 and prevention of infection among youth, while the attitudes and actions of youths were not significantly influenced by education intervention. Youth actively participated in empowerment activities for disseminating information related to COVID-19 on social media.